The Effect of Moringa Oleifera Leaf Juice on Drinking Water To Color, Protein, Fat, and Cholesterol Content of Yolk Egg of Lohmann Brown Chicken Age 22-30 Weeks - I K., Purnayasa; Warmadewi, D. A.; Siti, N. W. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The nutritional content of eggs important to increase knowledge of the community. This study aims to determine the effect of ( Moringa oleifera ) leaf water extract on color, protein, fat and cholesterol of Lohmann Brown chicken eggs aged 22-30 weeks. The study was conducted in laying hens in Dajan Peken Village, Tabanan Sub-district, Tabanan District, for 3 months using 36 Lohmann Brown laying chickens with a homogeneous weight maintained inside 18 plots of cages battrey coloni. The design used was Completely Randomized Design (RAL) with 3 treatments and 6 replications. The treatment was drinking water without Moringa leaf water extract (K0) as control, drinking water with 3% leaf water kelor leaf extract (K1), and drinking water with water extract of leaf of 6% (K2). The variables observed were yellow, protein content, fat content and cholesterol. The results showed that the color of yellow and protein content in K1 and K2 treatment were significantly different (P <0.05) higher than K0. However, the yolk fat and cholesterol levels in the K1 and K2 treatment were significantly lower (P <0.05) than the chickens not given ( Moringa oleifera ) leaf water extract. Based on research result that can be concluded giving extract of ( Moringa oleifera ) water leaf at level 3% and 6% through drinking water can increase yellow color and yolk protein level instead decrease and cholesterol level of chicken egg yolk Lohmann Brown aged 22-30 weeks.  Keywords: Moringa leaf water extract, eggs, chicken Lohmann Brown.